Rotações de tarefas baseadas nas cargas físicas e psicológicas: uma proposta para a indústria calçadista - Leite, Wilza Karla dos Santos (2021)
This thesis aims to propose models for task rotations in shoe production cells to minimize risk exposure to work-related musculoskeletal disorders (WMSDs) by integrating physical and psychological workloads. To this end, five articles were prepared. The first article aimed to analyze the factors related to health complaints and the severity of recurrence in workers in the footwear industry over a two-year period. The second aimed to analyze the factors related to absence and the indicators of illness in terms of recurrence and missed days in workers in the footwear industry. The third, to investigate the influence of biomechanical, psychosocial, environmental, and individual factors on local and multiple WMSD symptoms in footwear manufacturing workers. The fourth, to propose a model of task rotations in footwear production cells aimed at reducing exposure to the risk of WMSDs considering physical and psychological workloads. The fifth, to adapt into Portuguese the New Job Stress Scale (NJSS), which measures a set of work-related stressors. Different physiological and psychological dysfunctions are related to work in the footwear industry. However, neuromusculoskeletal and movement-related disorders tend to stand out in terms of severity. The illness seems to follow a seasonal pattern, concentrated in the last quarters of the years evaluated, and increases according to time and production demands. Physical and psychological overloads are associated with local and multiple WMSD symptoms and, when simultaneous, can increase the chances of its occurrence by up to dozens of times. The cutting, assembly and finishing sector is associated both with health complaints and time off work, and constitutes one of the sectors that demand longer recovery time before returning to work and a greater recurrence of symptoms. Therefore, the task rotation model was limited to the rubber sandals and sports shoes production cells within this sector. The solutions found in these models are capable of reducing the exposure to the risk of WMSD stemming from the physical and psychological workloads when compared to the conditions without rotations. However, it is also necessary to manage the risk of workloads, especially with regard to performing movements above the recommended ranges of motion, repetitiveness, work fragmentation, and low latitude of decision for workers. This thesis used the results of the abridged and adapted to Portuguese version of the Job Stress Scale (JSS) in the rotational models. Nonetheless, it also explored the validation in Portuguese language of a newer version entitled NJSS, which includes items not assessed by the JSS. The NJSS can be used in future studies to build new task rotation models.